(untitled) (BioLaw Journal - Rivista di BioDiritto, 2024)
Justice may be nearing its end with the advent of artificial intelligence. The ubiquitous penetration of AI, reinforced by its gaining legitimacy in non-obvious ways, is leading to a shift in the way humans perceive and apply the principles of justice. AI is incapable of truly understanding and interpreting the law, properly justifying decisions, or balancing rights and interests, which escapes public attention as people are excessively focused on its perceived perfection. Difficult to control, AI entails significant dependency of public institutions on private actors. Without undermining artificial intelligence as such, the article is calling to seriously rethink how far we are ready to go along this path.